A Hybrid Approach to Reconstruct a Complete TBP Curve from Blended Gas Condensates - Suhaimi, M; Naim, M. R (ASEAN Journal of Chemical Engineering, 2009)
Successful operations of a natural gas condensate fractionation unit requires the feed’s True Boiling Point (TBP) curve to be reconstructed and its’ bulk properties to be predicted. In this work, a hybrid approach combining the Generalised Distribution Model (GDM) and Pseudo-component Linear Equation (PcLE) methods are proposed. The proposed method is simple and requires limited information from readily available laboratory analysis data. The method was demonstrated using a refinery case study and found that the hybrid approach were able to reconstruct a pure component TBP curve from the blended feed data with error of less than 5%. Consequently the approach is very useful during preliminary stage for refinery engineers to explore and exploit the operational flexibility in a current distillation column to maximise the desired product yields.